Valved and Non-Valved Drainage Systems in the Surgical Treatment of Refractory Glaucoma - E. V. Karlova; M. V. Radaykina (Oftalʹmologiâ, 2019)
Purpose: to compare the efficacy and safety of Ahmed and Molteno-3 drainage devices implantation in the surgical treatment of refractory glaucoma. Patients and methods. Two groups of refractory glaucoma patients underwent surgery. In the first group (48 patients, 48 eyes) drainage device Molteno-3 with a site size of 175 mm2 was implanted. The average IOP in the group before surgery was 31.9 ± 7.7 mm Hg. The average number of glaucoma medications was 3.3 ± 0,44. In the second group (51 patients, 51 eyes) implantation of Ahmed Valve FP7 model was performed. The average level of IOP in the group before surgery was 34.7 ± 8.07 mm Hg. The average number of glaucoma medications was 3.08 ± 0.4. Results. In the first group the average intraocular pressure level 1 month post-op was 14.6 ± 6.1 mm Hg, 3 months post-op 18.8 ± 5.2 mm Hg, 6 months post-op 16.5 ± 4.7 mm Hg. IOP сompensation (≤ 21 mm Hg) in 6 months was achieved in 91.6 % of cases and in 1 year in 100 % of cases. The total success was achieved only in 8.3 % of patients. However, the number of glaucoma medications was reduced to 1.6 ± 0.8. In the second group the average IOP level 1 month post-op was 21.25 ± 7.3 mm Hg, 3 months post-op 17.9 ± 5.3 mm Hg, 6 months post-op 15.7 ± 4.1 mm Hg. IOP сompensation in 6 months was achieved in 82.4 % of cases and in 1 year in 86.3 %. In the second group complete success was achieved in 19.6 % of patients. The number of glaucoma medications was 1.4 ± 1.1. In the first group complications were revealed in 22.9 % of cases (11 patients). Ciliochoroid detachment was revealed in 9 patients (18,8 %) and hyphema in 2 patients (4,2 %). In the second group complications were revealed in 19.6 % of cases (10 patients). Сiliochoroid detachment was revealed in 4 patients (7.8 %), diplopia in 5 patients (9.8 %), hyphema was detected in one case (1.9 %). In the first group IOP compensation (≤21 mm Hg) was achieved after 6 months in 91.6 % of cases and after 1 year in 100 % of cases. The complete success was achieved in only 8.3 %. In the second group, IOP compensation in 6 months was achieved in 82.4 % of cases and 86.3 % — in 1 year. In the second group, complete success was achieved in 19.6 % patients. There was no significant difference in complications between two groups. Conclusion. High level of safety and effectiveness of refractory glaucoma surgical treatment with implantation of Molteno-3 and Ahmed drains was confirmed.